Analysis of the determinants of export performance in the spanish companies from the footwear industry - González-Ferriz, Fernando (Revista de Estudios Andaluces, 2021)
This investigation pretends to examine the behaviour of the exporting companies in the footwear sector, one of the most important in the eastern region of Spain, which generates sustainable added value through fashion. The testimony of the managers from a representative selection of companies will show the strengths and weaknesses of their internationalization processes, paying a special attention to variables like the international marketing strategy or the managerial function. On the other hand, the descriptive analysis of the most important determinants of export performance in the sector, will show that: (1) managers are well trained, (2) both the environment and firm characteristics will influence the marketing strategy, and (3) marketing policies incorporate relational elements and certain aspects of new technologies. This results in the evolution towards an environment based on services, where the study of market conditions will be decisive to identify customer needs in the best possible way. Finally, the contribution of theories like the Resourced Based View (RBV), the dynamic capabilities or the contingency theory will be crucial from the academic point of view.